Studi Fenomenologi: Pengalaman Keluarga Dengan Anggota Keluarga Yang Sudah Terkena Covid-19 - Ulfa Rahfiandhani Mardani; Sandra Sandra; Bayu Saputra (LPPM Hang Tuah Pekanbaru, 2023)
Coronavirus Disease 2019 (COVID-19) is a new type of virus with a high intensity of spreading and has been becoming the world’s health problem. People with Covid-19 need support from their families and communities, such as support in psychology, existence, relationship, growth necessity, community concern, and also supports in the religious sectors since they might affect the process of their recuperation. This research aims to explore and discover more deeply about an experience of a family whose members had already gotten infected by COVID-19. The research employed a qualitative approach with the phenomenology study method. The research participants were 8 people aged between 18 and 60 years old who were the main members of the family (father, mother, and children), and they lived in the same house along with the other members who had already been infected by COVID-19. The samples were hired by using the purposive sampling method. The data was collected by applying an interactively in-depth interview with the participants. The results of the research found that the psychological responses of the family when knowing its members got infected by COVID-19 caused the family to be anxious and frustrated. However, the spiritual responses given by the family made the fay to be more grateful and closer to God. Thus, the family and its members with covid-19 needed social support form of motivation as well as support in the fulfillment of basic needs, family affections, and medicines. It was concluded that the family's experience with family members who have been affected by COVID-19, can be an illustration, for other families when facing the same problem.